Normal pre-eruptive inclinations of maxillary canine, lateral incisor, and first premolar in children aged 6-14 years - Santosh K Goje; Bhavna Dave (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Maxillary canine is the second most common tooth that gets impacted after III molars. Early pre-eruptive inclination changes of first premolar and its associative changes with canine inclination are an important factor that predicts the fate of maxillary canines. Hence, a cross-sectional study was planned to evaluate the normal pre-eruptive mesiodistal inclinations of maxillary permanent canine, first premolar, and lateral incisor in children aged 6-14 years using orthopantomogram. MATERIALS AND METHODS: The total number of participants was 296. Each group of boys and girls consisted of 37 participants in each of the age groups 6-8 years, 8-10 years, 10-12 years, and 13-14 years, making up a total of 148 boys and 148 girls. Routine clinical examination was conducted, and orthopantomograph was taken for radiographic examination. Orthopantomographs of all these participants were collected. Inclination of lateral incisor, inclination of canine, and inclination of premolar with midline were measured on the orthopantomogram. Also, the angles between the canine with lateral incisor and canine with first premolar were measured. Pearson correlation was also evaluated between the movement of canine with lateral incisor and canine with first premolar. RESULTS: All the mean angles related to lateral incisor, canine, and first premolar with midline were recorded. Also, the angles between the canine with lateral incisor and the canine with first premolar were recorded. The movements between lateral incisor, canine, and first premolar were moderately correlated from 6 to 12 years of age. CONCLUSION: The eruption of canine from the floor of the nose till it erupts has its synchronized influence on the lateral incisor and the first premolar.